2015
DOI: 10.14306/renhyd.19.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Semáforo nutricional: conocimiento, percepción y utilización entre los consumidores de Madrid, España

Abstract: Introducción: Describir el grado de conocimiento, comprensión, percepción y utilización del semáforo nutricional entre los consumidores madrileños. Material y Métodos: Estudio transversal realizado en dos fases en el año 2012. Se reclutaron consumidores madrileños de forma aleatoria en zonas de espera de 7 supermercados. Mediante un cuestionario, se recogió información referente al conocimiento, percepción y utilización del semáforo nutricional. Se procedió al cálculo de porcentajes de las variables de interés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
1
2
0
2
Order By: Relevance
“…The authors reported that consumers easily relate green to the best option and red to the worst but yellow causes doubt. A similar finding was reported by León‐Flández et al (2015) who found that Spanish consumers had a low comprehension of the traffic light system. In a study conducted in Germany, Borgmeier and Westenhoefer (2009) observed that when the traffic light label is used in conjunction with other labels, consumers may find the excess information hard to use, in line with the results of this review.…”
Section: Discussionsupporting
confidence: 88%
“…The authors reported that consumers easily relate green to the best option and red to the worst but yellow causes doubt. A similar finding was reported by León‐Flández et al (2015) who found that Spanish consumers had a low comprehension of the traffic light system. In a study conducted in Germany, Borgmeier and Westenhoefer (2009) observed that when the traffic light label is used in conjunction with other labels, consumers may find the excess information hard to use, in line with the results of this review.…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with our results, a study in Spain showed based on subjective data that 41.4% of the participants knew about the NTLL, 61.5% of which stated that the NTLL seemed useful and 31.4% referring a usual use of it. In addition, the study also showed that 18.6% of the participants correctly understood the NTLL information [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, consumers found it difficult to interpret the meaning of the yellow traffic light. Spanish consumers also found it difficult to understand the traffic light system (Le on-Fl andez et al, 2015).…”
Section: Discussionmentioning
confidence: 99%